2015
DOI: 10.1093/jxb/erv421
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression ofOsCYP19-4increases tolerance to cold stress and enhances grain yield in rice (Oryza sativa)

Abstract: HighlightOsCYP19-4 is a novel apoplastic immunophilin that plays a role in developmental acclimation and cold stress, probably via regulation of auxin transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 54 publications
3
37
0
Order By: Relevance
“…In addition, protein-protein interaction analysis showed that the psbQ-like protein 1 was interacted with another up-regulated protein PPI (A0A0K9RJJ3 |peptidyl-prolyl cis-trans isomerase fkbp16-4) ( Figure 4a). The same up-regulation has been shown in other studies [19] which imply that plants may respond to salt stress by accumulating PPI to accelerate protein synthesis. Another up-regulated protein A0A0K9QN40 is thioredoxin Y1 that has the ability to regulate the activity of photosynthetic enzymes [20] .…”
Section: Analysis Of the Daps Response To Salt Stress In Chloroplastsupporting
confidence: 84%
“…In addition, protein-protein interaction analysis showed that the psbQ-like protein 1 was interacted with another up-regulated protein PPI (A0A0K9RJJ3 |peptidyl-prolyl cis-trans isomerase fkbp16-4) ( Figure 4a). The same up-regulation has been shown in other studies [19] which imply that plants may respond to salt stress by accumulating PPI to accelerate protein synthesis. Another up-regulated protein A0A0K9QN40 is thioredoxin Y1 that has the ability to regulate the activity of photosynthetic enzymes [20] .…”
Section: Analysis Of the Daps Response To Salt Stress In Chloroplastsupporting
confidence: 84%
“…In previous studies, we showed that several plant IMMs function in various subcellular organelles, such as cytosol, apoplast, chloroplast, and Golgi apparatus, as positive regulators of the abiotic stress response (Park et al , ; Seok et al , ; Lee et al , ; Yoon et al , ; Park et al , ). In rice, OsFKBP20‐1b is the most inducible IMM under water stress (Ahn et al , ), and is also responsive to other abiotic stresses (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Rice (Oryza sativa), as a dietary staple for almost two-thirds of the world's population, is one of the most important agricultural crops. Recently, some genes have been used successfully to improve the tolerance of rice to stresses [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%